Evaluation of the phenotypic performance of a Red Maasai and Dorper double backcross resource population: Indoor trickle challenge with Haemonchus contortus - Mugambi, J.M.M.; Audho, James O.; Njomo, S.; Baker, R.L. (Elsevier, 2005)
Six F1 Dorper (D) x Red Maasai (R) rams were mated to both D and R ewes to produce backcross lambs. These six double backcross resource families are being analysed to identify quantitative trait loci that may be controlling resistance to gastro-intestinal (GI) nematode parasites, mainly Haemonchus contortus. After assessing the phenotypic performance of the lambs following exposure to natural infections, the surviving lambs were drenched and moved indoors for an artificial challenge with H. contortus along with straightbred D and R lambs. A total of 1317 lambs were included in the analyses consisting of 523 3/4D, 580 3/4R, 87 D and 127 R. The D lambs were significantly and consistently heavier than R lambs and 3/4D were significantly heavier than the 3/4R lambs. The difference between the backcrosses was about half of that between the straightbreds. Resistance was assessed in terms of faecal egg counts (FEC) and total worm counts (TWC) at necropsy while packed cell volume (PCV) was used to assess resilience to weekly oral doses of 2500 infective larvae of H. contortus. No significant breed differences were observed for log transformed FEC (LFEC). A significant breed difference in PCV was recorded. The backcrosses had the higher values and while no differences were observed between the straightbreds, 3/4D had significantly higher PCV than the 3/4R. Despite the absence of breed differences in FEC the R and the 3/4R had significantly fewer worms than the D and the 3/4D. The D had significantly longer worms than the R and the 3/4D had significantly longer worms than the 3/4R. Worms recovered from D had more eggs than those recovered from R. Similarly worms from 3/4D contained more eggs than those from 3/4R. Thus, on a breed basis the breed with more worms had longer worms. In contrast, when, in a small part of the experiment two doses of larvae were used to check for any breed by dose interactions, worms from the low dose (and hence fewer worms) animals were longer. We postulate that in fast growing hosts like the D, worms also have a better potential for growth and reproduction than in hosts that have less potential for growth. The overall correlation coefficient between PCV and LFEC was -0.67 while that between LFEC and LTWC was 0.72. From these results it is clear that the R do not respond to the artificial challenge the way they do to natural infection suggesting that phenotyping of R and R cross lambs for purpose of selecting those that are resistant or susceptible is best done under natural challenge.